Children's experiences of visiting av seriously ill/injured relative on an adult intensive care unit - Interviews with 22 children who has visited a relative in an adult intensive care unit - Bergbom, Ingegerd; Knutsson, Susanne (University of Gothenburg, 2019)
AIM: This paper is a report of a study of children's experiences of visiting a seriously ill/injured relative in an intensive care unit.

BACKGROUND: Little attention has been paid to children's experiences and needs when visiting a relative being cared for at a high technological adult intensive care unit. Instead, the focus has been on adult's experiences and needs.

METHOD: In 2004, 28 children (14 girls, 14 boys) aged 4-17 years who had visited an adult relative were interviewed 3 months after the visit. A hermeneutic approach was used when interpreting and analysing the text.

FINDINGS: Four themes were generated from the data: It meant waiting, It was strange, It was white and It was good. Waiting was experienced as difficult, increasing the feeling of uncertainty, exclusion and separation, which in turn led to tension and concern. 'It was strange' was perceived as unfamiliar but also with interest and curiosity. The experience of the intensive care unit was that it was white. Everything in the patient's room was experienced as white and gloomy. It lacked joy. 'It was good' was stated about the outcome of the visit because through this they were given the opportunity to meet and see the relative by themselves. This evoked feelings of relief and joy. The visit did not seem to frighten the child; instead it generated feelings of release and relief.

CONCLUSION: Children's experiences of visiting an adult intensive care unit seem to support theories that emphasize the involvement and participation of children in family matters.

Purpose:

To describe and understand children’s thoughts and feelings related to visiting critically ill relatives or family members in an adult intensive care unit.

Interviews with 22 children who has visited a relative in an adult intensive care unit

Syfte: Artikeln är en rapport om en studie av barns erfarenheter av att besöka en allvarligt sjuk/skadad släkting på en intensivvårdsavdelning.
Bakgrund: Lite uppmärksamhet har ägnats åt barns erfarenheter och behov när de besöker en släkting som vårdas vid en högteknologisk vuxenintensivvårdsavdelning. Istället har fokus legat på de vuxnas behov och erfarenheter.
Metod: 2004 intervjuades 28 barn (14 flickor och 14 pojkar) i åldrarna 4-17 år som hade besökt en vuxen släkting, tre månader efter besöket. En hermeneutisk förhållningssätt har används när data har analyserats och tolkats.
Resultat: Fyra teman identifierades vid analysen av data: Det innebar väntan, Det var underligt/främmande, Det var vitt och Det var bra. Väntan upplevdes som svårt och ökade känslan av osäkerhet, utanförskap och separation, vilket i sin tur ledde till anspänning och oro. "Det var underligt/främmande" uppfattades som något okänt men också som intressant och med nyfikenhet. Upplevelsen av intensivvårdsavdelningen var att den var vit. Allting i patientens rum upplevdes som vitt och tråkigt. Det saknade glädje. "Det var bra" handlar om besökets konsekvenser som innebar att barnen fick träffa och se släktingen själva. Detta gav känslor av glädje och lättnad.
Slutsats: Barns upplevelser av att besöka en vuxen på intensivvårdsavdelning verkar stödja teorier som framhåller vikten av att barn är delaktiga i familjens angelägenheter.

Syfte:

Att beskriva och förstå barns tankar och känslor relaterade till besök hos allvarligt sjuka/skadade släktingar eller familjemedlemmar på intensivvårdsavdelning.

22 intervjuer med barn som besökt en släkting på en vuxenintensivvårdsavdelning
Barns erfarenheter av att besöka allvarligt sjuka/skadade släktingar på en vuxenintensivvårdsavdelning - Intervjuer med 22 barn som besökt en äldre släkting på en vuxenintensivvårdsavdelning
Keywords: children; barn; Emotions; Emotioner; Family; Familj; Critical Care; Vård vid livshotande sjukdom; Intensive Care Units; Intensivvårdsavdelningar; Qualitative Research; Kvalitativ forskning; Hermeneutics; Hermeneutik; HEALTH; HÄLSA; Medical and Health Sciences; Medicin och hälsovetenskap